Stalin and war, 1918-1953 - Shearer, David R., 1952- author.
1 online resource.
Keywords: "Stalin and War, 1918-1953 is the first book to examine the patterns of radicalized internal violence that characterized the Stalinist regime across the whole of the dictator's rule, and it is one of the only works to connect patterns of internal violence to the dictator's perceptions of war and foreign threat. This book will be of interest to professional scholars of Soviet history, twentieth-century history, and World War II history, and it is approachable enough to be appreciated by general readers"--